Netnographic research in understanding social media as a new public sphere - Palupi, Anggi Trivina (C-DISC, 2024)
The development of information and communication technology and new media has brought a new dimension of public space to society. In the 19th century, the realization of a public space that really facilitated public communication was very limited due to the domination of public space by the state and industrial corporations. However, with the existence of the Internet, it is possible for a new public space or new public sphere called social media to emerge. The emergence of social media has succeeded in changing people’s interaction and communication patterns from offline to online. This has implications for the emergence of social media phenomena, both positive and negative. In order to understand the facts of sociality in online spaces or social media, a new research method technique called netnography is needed. Netnography is present as a lens and mitigator for various forms of changes in interaction and communication patterns in online spaces, which ultimately give rise to a new online culture.